2023
DOI: 10.1111/ijfs.16716
|View full text |Cite
|
Sign up to set email alerts
|

Effects of highland barley protein and β‐glucan addition on the flour structure, bread quality and starch digestibility of whole wheat bread

Qi Zhang,
Yueyue Yang,
Zhengyu Jin
et al.

Abstract: SummaryWhole wheat bread is rich in nutrition, but its starch digestibility is unsatisfactory. Thus, how to reduce its digestibility has attracted much attention. This study investigated the effects of highland barley protein and β‐glucan on the pasting properties, and thermal properties of whole wheat flour to reveal the mechanism of highland barley protein and β‐glucan regulating the in vitro digestibility. The digestibility results showed that β‐glucan and protein could slow down starch digestion to some de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Pan et al (2021) found that the hardness and springiness of catechinadded steamed bread were reduced and the chewiness increased. Zhang et al (2023) also showed that the addition of barley protein increased the hardness and chewiness and decreased the cohesiveness of bread. Dietary fibre thickened the walls around the air chambers in the bread crumbs, which strengthened the gluten backbone thereof.…”
Section: Effects Of Dietary Fibre-polyphenol-protein Complex On Textu...mentioning
confidence: 93%
See 1 more Smart Citation
“…Pan et al (2021) found that the hardness and springiness of catechinadded steamed bread were reduced and the chewiness increased. Zhang et al (2023) also showed that the addition of barley protein increased the hardness and chewiness and decreased the cohesiveness of bread. Dietary fibre thickened the walls around the air chambers in the bread crumbs, which strengthened the gluten backbone thereof.…”
Section: Effects Of Dietary Fibre-polyphenol-protein Complex On Textu...mentioning
confidence: 93%
“…protein-starch gel formed by the protein and starch chains could give the sample a higher hardness value and the addition of protein led to the disruption of the gluten structure and the formation of a denser pore structure (Ni et al, 2020;Pan et al, 2021;Meng et al, 2022;Zhang et al, 2023).…”
Section: Effects Of Dietary Fibre-polyphenol-protein Complex On Textu...mentioning
confidence: 99%